Comparison of laparoscopic single-site surgery and traditional laparoscopic surgery for endometrial cancer - DENG Yuan; DENG Li; YAO Yuanyang; TANG Shuai; TAN Wenwei (Di-san junyi daxue xuebao, 2022)
Objective To compare the perioperative outcomes of laparoscopic single-site surgery (LESS) versus traditional laparoscopic surgery (TLS) in the staging surgery of endometrial cancer, and to verify its safety, feasibility and effectiveness. Methods A total of 535 patients diagnosed with endometrial cancer and undergoing laparoscopic total staging surgery from August 2018 to August 2020 in our department were retrospectively recruited in this study. Among them, 26 patients underwent LESS, and 509 received TLS.A 1∶2 propensity score matching was performed to minimize the bias due to the imbalanced baseline features between the 2 groups. Finally, 26 cases in LESS group and 52 cases in TLS group were obtained. The operation time, volume of intraoperative blood loss, number of lymph nodes removed, time of postoperative exhaust, time of postoperative indwelling drainage, postoperative hospital stay, pain score of 24-hour after surgery and satisfactory with cosmetic results were analyzed and compared between the 2 groups. Results The operations in both groups were successfully completed without conversion to laparotomy. There were no statistical differences in the volume of intraoperative blood loss, number of lymph nodes removed, time of postoperative exhaust, time of postoperative indwelling drainage, and postoperative hospital stay between the 2 groups. Meanwhile, the LESS group has significantly longer operation time (197.3±55.7 vs 164.7±62.7 min), a lower pain score of 24-hour after surgery and a more satisfactory postoperative cosmetic effect (5.73±0.53 vs 5.17±0.71) when compared with the TLS group (P < 0.05). Conclusion Compared with TLS, LESS is safe and feasible for endometrial cancer, with advantages of less pain and good cosmetic effectiveness.